Tie-in configuration as a strategy for correction of transverse humerus fracture in striped owl (Asio clamator) - Case report (Research, Society and Development, 2022)
The purpose of this report is to describe a surgical case of correction of a transverse fracture in the humeral diaphysis of striped owl (Asio clamator) using the hybrid fixation technique (tie-in configuration). describing the conditions for the chosen conduct and the positive results in the treatment of this type of fracture in this species. In the methodology, it was reported, in a striped owl (Asio clamator), from a rescue after a collision accident with a residence, attended at the Veterinary Hospital of the INTA University Center (HOVET-UNINTA) presenting difficulty in perching, paresis, wings asymmetrical and drooping. As a result of the clinical and surgical care, after stabilization, a radiographic examination was performed in ventro-dorsal projection, showing the presence of a complete transverse fracture in the left humeral diaphysis. Then, the tie-in conformation was used to stabilize the fracture. From this case, it was observed that the use of the tie-in configuration can be an effective alternative in these cases, demonstrating recovery of the animal after the post-surgical period.